Komponen Kimia Serat Daun Doyo (Curliglia latifolia): Chemical Properties of Doyo (Curliglia latifolia) Leaf Fibers - Marwanto, Marwanto; Nurhaida, Nurhaida; Masruchin, Nanang (PERENNIAL, 2024)
Local communities widely use natural fibers to fulfill their daily needs. Doyo leaf fibers are fibers used by the people of Kalimantan for clothing and weaving traditional mats. This research analyses the fundamental properties of doyo leaf fibers, including chemical components, functional groups, and crystallinity index. The soluble extractive content of polar solvents was higher than the extractive content of non-polar solvents in doyo leaf fibers. The holocellulose content of doyo leaves is 60.47. The α-cellulose for doyo leaves was 53.51. The lower the α-cellulose yield, the more hemicellulose content dominates the fiber. The FTIR test results also support the chemical component test results. The high alpha cellulose content will affect the fiber’s crystallinity index. Doyo leaf fiber has a degree of crystallinity of 69.77%. Doyo leaf fiber is suggested as the raw material for crystalline nanocellulose.